Socio-Economic Status and Health Seeking Behaviour Among the People of Rural Areas of Pangsha Upazila ofRajbari District, Bangladesh - Sharmin, Saida; Sultan, Zobayed; Haque, Kazi Mahbubul (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Health seeking behaviour is an important factor in health management. Socioeconomic status is having greater impact on health care utilization especially in developing countries. Objective: To identify the socioeconomic factors of rural community people and their health care seeking behaviour. Methods: The descriptive, cross-sectional study was conducted in Pangsha upazila of Rajbari district in Bangladesh, between January 2018 and February 2018. A total of 317 purposively selected people were interviewed face to face using a pre-tested semi-structured questionnaire. Results: In this study, majority 98 (30.91%) of the respondents were within the age group of below 31 years (41.47±15.12). More than two-thirdsi.e. 218 (68.76%) of the respondent was male and majority 205 (64.50%) belonged to nuclear family. Most of the respondents were married 283 (89.00%) and 227 (71.40%) of the respondents were Muslim. Majority 149 (47.00%) of the respondents’ monthly income was between 10000 and 20000 Bangladeshi Taka. Among all respondents, majority 60 (18.92%) people sought treatment for fever. 193 (60.89%) used to visit private health facility. 181 (56.9%) people took treatment by MBBS doctor and 205 (64.50%) of the respondents choose the specific health facility for the reason of better treatment. Conclusion: Health seeking behaviour of people in this study was appreciable. In this study, people received treatment from private health facility. The perception of the people has to be changed to attract them more to government hospitals. It can be done through improving the quality of care, proper maintenance of facilities.Awareness raising activities, and education for health behaviour change are also recommended. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 188-192